A HISTORY OF MOROCCAN ARABIC STUDIES (Romano-arabica, 2025)
The first recorded studies on Moroccan Arabic date back to the late 19th century, as a consequence of the interest of the French administrators and Orientalists who were focused on Morocco’s political and economic importance to France. These first studies aimed to report grammatical descriptions and transcriptions of spoken varieties. Since its beginning, the 20th century brought a more extensive attentiveness in understanding the local language varieties of the colonised North Africa, which led to more systematic studies that described Moroccan Arabic phonetics and phonology, as well as comparative observations on the Maghrebi varieties. After World War II, European linguists introduced a modern approach in Moroccan dialectology and sociolinguistics, discovering relationships between different Moroccan Arabic varieties and documenting regional ones. The 21st century studies keep pace with the modern reality in the Moroccan society, revealing cultural, sociolinguistic, educational, and socio-political influences in the spoken Moroccan Arabic.